Controversy of Adopted Children Status and Foster Father in the Marriage Process Based on Islamic Law Perspective - Fauzi, Ahmad; Indrajaya, Darmawan Tia; Zikri, Ahmad; Zulfahmi, Zulfahmi; K, Hendri (Journal of Progressive Law and Legal Studies, 2023)
This paper seeks to explain the controversy regarding the status of adopted children and adoptive fathers in a marriage procession by using a normative juridical approach, it is concluded that the status and position of adopted children in the Islamic legal system does not break the kinship relationship between the adopted child and his biological parents so that the adoptive father does not become the guardian of his adopted child except through the mandate given by the child's biological parents. This study uses a normative approach and method, conducted by examining theoretical matters concerning Islamic legal norms and positive law. Primary sources are the Koran, hadith, Compilation of Islamic Law, and Marriage Laws. Secondary sources refer to the opinions of experts, as well as references related to the issues raised. The results of this study explain that the validity of the marriage guardian for adopted children is to remain with the lineage guardian if his whereabouts are still known and cannot be replaced by anyone except the lineage guardian is unknown, then the marriage guardian can be replaced by a judge's guardian. However, if in practice the adopted child is not known who the biological parents are, then the adopted daughter's marriage guardian is the adoptive father, or if the adoptive father receives a mandate from the child's biological father, then the marriage is valid as stated by al-Bahuti